Peningkatan Kemampuan Numerasi Peserta Didik Menggunakan Pembelajaran Blended Learning Berbantuan Whole Number Board pada Materi Bilangan Cacah di Kelas V Sekolah Dasar Negeri 3 Sokanegara Tahun Ajaran 2024/2025 - Wardani, Fitrian Prila; Yanuarto, Wanda Nugroho; Purwani, Purwani (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to apply the blended learning model assisted by the whole number board and improve the numeracy skills of students in the material of whole numbers of class V of SD Negeri 3 Sokanegara in the 2024/2025 academic year. This research was conducted in April - May 2025. The method used in this study is classroom action research (CAR). This method is carried out in four stages, namely planning, implementation, observation and reflection of action. The four stages are cycles that take place repeatedly and are carried out with the same steps. Based on the results of the study, it was concluded that the blended learning model assisted by the whole number board can improve the numeracy skills and learning independence of students in the material of whole numbers of class V of SD Negeri 3 Sokanegara in the 2024/2025 academic year. This is indicated by the increase in students' numeracy skills pra cycle by 43% in cycle I by 70% and cycle II by 91%.